The impact of sustainable tourism on local community cultural heritage conservation awareness in Hanoi - Tri Phuong Nguyen (Heritage and Sustainable Development)
The current research analyzes the effect of sustainable tourism on the cultural heritage preservation awareness of the local communities in Hanoi, Vietnam. The study is based on data collected from 245 respondents, revealing the relationships using SPSS 26.0 and SmartPLS 4.0. It is discovered that there are sustainable tourism components and cultural heritage awareness components, and behavioral change is a significant mediating variable. The path coefficient from behavioral change to awareness is 0.410 (T = 6.091, P < 0.001), which shows a strong direct effect. Additionally, knowledge about sustainable tourism (KNO) shows a significant indirect effect on awareness through behavioral change, with an effect size of 0.091 (T = 2.746, P = 0.006). Local residents’ participation (LRP) demonstrates the strongest indirect impact with a coefficient of 0.146 (T = 4.687, P < 0.001), emphasizing the importance of community engagement. The R² value for behavioral change is 0.453, suggesting a moderate explanatory power, while the R² for awareness is 0.168, indicating a weaker yet meaningful contribution. Predictive relevance assessed by Q² reveals medium accuracy for behavioral change (Q² = 0.297) and small predictive capacity for awareness (Q² = 0.116). The results support the hypothesis that a change in behavior is instrumental in connecting sustainable tourism practices with increased concern for the preservation of cultural heritage. These impacts denote the contribution of this study, which seeks to explain how sustainable tourism shifts local perceptions about the culture of the place. It underscores the role of education combined with active involvement, as well as policies aimed at promoting identity-preserving sustainability initiatives. Addressing these gaps, policymakers need to emphasize tourism development that fosters community engagement and empowerment, particularly in relation to conservation in Hanoi.